How do ED patients with criminal justice contact compare with other ED users? A retrospective analysis of ED visits in California. Issue 6 (21st June 2018) - McConville, Shannon; Mooney, Alyssa C; Williams, Brie A; Hsia, Renee Y
Abstract : Objective: To assess the patterns of emergency department (ED) utilisation among those with and without criminal justice contact in California in 2014, comparing variation in ED use, visit frequency, diagnoses and insurance coverage. Design: Retrospective, cross-sectional study. Setting: Analyses included ED visits to all licensed hospitals in California using statewide data on all ED encounters in 2014. Participants: Study participants included 3 757 870 non-elderly adult ED patients who made at least one ED visit in 2014. Primary and secondary outcome measures: We assessed the patterns and characteristics of ED visits among those with criminal justice contact—patients who were either admitted to or discharged from the ED by a correctional institution—with patients who did not have criminal justice contact recorded during an ED visit. Results: ED patients with criminal justice contact had higher proportions of frequent ED users (27.2% vs 9.4%), were at higher risk of an ED visit resulting in hospitalisation (26.6% vs 15.2%) and had higher prevalence of mental health conditions (52.8% vs 30.4%) compared with patients with no criminal justice contact recorded during an ED visit. Of the top 10, four primary diagnoses among patients with criminal justice contact were related to behavioural health conditions, accounting for 19.0% of all primary diagnoses in this population. In contrast, behavioural health conditions were absent from the top 10 primary diagnoses in ED patients with no observed criminal justice contact. Despite a high burden of disease, a lack of health insurance coverage was more common among those with criminal justice contact than those without (41.3% vs 14.1%). Conclusions: Given that a large proportion of ED patients with criminal justice contact are frequent users with considerable mental health conditions, current efforts in California's Medicaid programme to identify individuals in need of coordinated services could reduce costly ED utilisation among this group.